The mouse Runx1 +23 hematopoietic stem cell enhancer confers hematopoietic specificity to both Runx1 promoters. - Bee, T; Ashley, E; Bickley, SR; Jarratt, A; Li, P; Sloane-Stanley, J; Göttgens, B; de Bruijn, M (2009)
The transcription factor Runx1 plays a pivotal role in hematopoietic stem cell (HSC) emergence, and studies into its transcriptional regulation should give insight into the critical steps of HSC specification. Recently, we identified the Runx1 +23 enhancer that targets reporter gene expression to the first emerging HSCs of the mouse embryo when linked to the heterologous hsp68 promoter. Endogenous Runx1 is transcribed from 2 alternative promoters, P1 and P2. Here, we examined the in vivo cis-regulatory potential of these alternative promoters and asked whether they act with and contribute to the spatiotemporal specific expression of the Runx1 +23 enhancer. Our results firmly establish that, in contrast to zebrafish runx1, mouse Runx1 promoter sequences do not confer any hematopoietic specificity in transgenic embryos. Yet, both mouse promoters act with the +23 enhancer to drive reporter gene expression to sites of HSC emergence and colonization, in a +23-specific pattern.